(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2015)
Introduction: Posterior urethral valve (PUV) is the most frequent cause of urethral obstruction in male child. These lesions usually result in lifelong disabilities with incontinence and decreased renal function despite optimal medical management. Primary fulguration without upper tract diversion is the preferred modality of treatment in most cases of PUV. Regular follow-up is needed to check completion of valve fulguration, renal function, status of hydronephrosis, vesicoureteric reflux (VUR), urinary tract infection (UTI), and bladder function. Materials and methods: We conducted interventional study among 30 purposively selected patients of PUV in the Department of Pediatric surgery, Dhaka Medical College Hospital (DMCH), Dhaka, over a period of 20 months from December 2009 to July 2011. Age of study subjects varied from 2 days to 14 years. Among the 30 patients, 16 were children in the age group between 1year to14 years (53.3%), 11(36.7%) were infants and the rest 03(10%) were neonates. Most of the patients presented with weak urinary stream, dribbling of urine, straining at micturition, UTI and palpable bladder. All children were subjected to ultrasonography (USG), blood urea, serum creatinine, routine urine examination and culture studies. Structured questionnaire was used to collect information regarding improvement or disappearance of VUR and renal functional status before & after primary fulguration of PUV. Results: Average serum creatinine level was found gradually decreased in subsequent follow up in comparison with the previous one. This difference of creatinine level was found statistically significant in t-test (p<0.01). Average blood urea nitrogen (BUN) was also decreased which was found statistically significant (p<0.05). VUR was present in 63.3% cases. Non- VUR was found in 60% cases on right side and 50% cases on left side. On the third follow-up after 3 months it became 73.3% on right side and 63.3% on left side. Positive correlation found in Pearson correlation test about the changes of reflux grades before and after fulguration was significant at the level of 0.01(p<0.001). It was significant on both left and right kidneys. Positive correlation found in Pearson correlation test about the changes of GFR before and after fulguration was also significant at the level of 0.01(p <0.001). Collected data was cleaned, edited and analyzed with the help of software SPSS window version 15.0. Conclusion: In this study, VUR disappeared in some cases and decreased in majority of the cases by 3 months after adequate restoration of urethral patency. Renal function came to normal range in two thirds of the cases. J. Paediatr. Surg. Bangladesh 3(2): 71-77, 2012 (July)